Non-structural carbohydrate dynamics of Pinus yunnanensis seedlings under drought stress and re-watering - Xiao, Jiandong; Zhao, Zhijuan; Deng, Xin; Hu, Haocheng; Liu, Yuanxi; Sun, Jianli; Fu, Xiaoyong; Wu, Junwen (Frontiers in Ecology and Evolution, 2024)
Non-structural carbohydrates (NSC) are an important "buffer" for maintaining plant physiological functions under drought conditions; however, our understanding of the dynamics of NSC at the organ level during sustained drought of varying intensities and re-watering remains poor. In this study, two-year-old Pinus yunnanensis seedlings were subjected to drought and re-watering trials. Plants were subjected to three drought intensities (light drought, moderate drought, and severe drought) as well as control conditions (suitable moisture) for 51 days, including 30 days of drought followed by 21 days of re-watering for drought-treated seedlings, to study the dynamics of NSC in the leaves, stems, coarse roots, and fine roots. Changes in the distribution of NSC concentrations in the organ of P. yunnanensis seedlings under drought stress varied; in the early drought stages, the drought resistance of P. yunnanensis seedlings was enhanced by increasing soluble sugar concentrations; in later stages of drought, the stored starch in organs, stems, and coarse roots was consumed. Drought inhibited the growth of P. yunnanensis seedlings, but the maximum limit of drought tolerance was not reached under the different drought treatments after 30 days. P. yunnanensis seedlings in all treatment groups resumed growth after re-watering, and the growth of seedlings was actually promoted during re-watering in the moderate drought treatment group, indicating that drought induced the compensatory growth of seedlings. The growth of P. yunnanensis seedlings during re-watering was inhibited in the severe drought treatment group, and NSC continued to be regulated in seedlings in this group. Given that P. yunnanensis seedlings maintain growth through the consumption of coarse root starch in the late stages of drought, seedlings with a larger root-to-shoot ratio should be selected for cultivation in actual production. Based on our findings, exposure to moderate drought stress can enhance the drought tolerance of P. yunnanensis seedlings and promote the compensatory growth of seedlings.